Anomalous mode-converting reflection of elastic waves using strip-type metagratings. (1st March 2023) - Kim, Shin Young; Oh, Yu Bin; Lee, Joong Seok; Kim, Yoon Young
Highlights: A novel metagrating for simultaneous realization of mode-converting and anomalous steering of elastic wave reflection is proposed. Near-perfect mode-conversion efficiencies are achieved for in-plane waves in thin elastic plate. Metagratings realize longitudinal-to-shear and shear-to-longitudinal wave mode conversions in scattered refection field. Higher-order scattered diffraction modes are effectively and selectively suppressed in metagratings. Abstract: Metasurfaces have recently received much attentions for manipulating waves. However, it is difficult to control all high-order or diffracted modes using the popularly employed metasurfaces. Herein, we propose a new way for converting a normally incident elastic longitudinal (or shear) wave mode to an obliquely reflected elastic shear (or longitudinal) one, using metagratings of elaborately designed and arranged strips. For a longitudinal (or shear) wave incidence upon the free end of an elastic plate, it is intrinsically difficult to realize full-power mode conversion and steer the converted mode without generating undesired reflected waves. We show that our elaborately designed and optimized multiple rectangular strip-type metagratings are effective in simultaneously fulfilling the mode conversion and anomalous steering of elastic waves. Unlike metasurfaces, the proposed metagratings operate via the diffraction theory and multiple rectangular strips permit sufficient design freedom to fulfill the two design objectives. Several numerical simulations in this work show that the proposed strip-type metagratings achieve near-perfect mode-conversion efficiencies reaching 96 %, and the performance is supported by experiments. Applications of the designed metagratings in nondestructive evaluation are also demonstrated.